Aplicação de processo oxidativo avançado na remoção do herbicida atrazina - Dantas, Ádila de Oliveira Sampaio (2021)
Brazil is the fifth country with the largest consumption of pesticides in the world and one of the main herbicides used is atrazine (ATZ), with a maximum residue limit (MRL) of 2 μgL-1. Yet, ATZ is banned throughout the European Union and many countries due to its high potential for water and soil contamination, being considered an emerging pollutant (EP) due to its endocrine disruptor characteristic. Current water and wastewater treatments are not suitable to degrade highly recalcitrant organic pollutants such as ATZ, thus, Advanced Oxidative Processes (AOPs) emerge as a viable alternative for mitigating these compounds. This present work has as an object of study the AOPs using photolysis (UV), peroxidation (H2O2), photoperoxidation (UV / H2O2), Fenton, and photo-Fenton in degradation of ATZ. In the UV/H2O2 processes, the condition at pH 5.0 was the most effective with 53.42% degradation of ATZ. Yet, Fenton and photo-Fenton experiments at pH 3.0 have obtained removal efficiencies of ATZ of 69.84 and 78.87%, respectively. The main process variables were analyzed using statistical tools through two factorial designs and one central composite design (CCD). Considerable removals of ATZ obtained for photolysis, peroxidation, photo-peroxidation, and Fenton, however, there was an emphasis for photo-Fenton reactions with an efficiency of 93.77% degradation of ATZ and 17.04% residual H2O2, a condition supposed to be ideal from CCD. Response analysis of ATZ removal percentage, the results were considered statistically significant (p ≤ 0.05). As for the response percentage of residual peroxide hydrogen, the ratio x1 = [Fe2+]/[H2O2] is the source of variation which dictates the response behavior. The ideal multiple response condition was obtained from the Desirability function, and the calculated and real parameters are closely related showing a fit in the validation experiment. However, phytotoxicity with Lactuca sativa suggests that there are toxic byproducts formation in the posttreatment effluent.